Proteomic signature profiling in the cortex of dairy cattle unravels the physiology of brain aging - Cozzolino, Flora; Canè, Luisa; Gatto, Maria Claudia; Iacobucci, Ilaria; Sacchettino, Luigi; De Biase, Davide; Di Napoli, Evaristo; Paciello, Orlando; Avallone, Luigi; Monti, Maria; d’Angelo, Danila; Napolitano, Francesco (Frontiers in Aging Neuroscience, 2023)
Introduction Aging is a physiological process occurring in all living organisms. It is characterized by a progressive deterioration of the physiological and cognitive functions of the organism, accompanied by a gradual impairment of mechanisms involved in the regulation of tissue and organ homeostasis, thus exacerbating the risk of developing pathologies, including cancer and neurodegenerative disorders. Methods In the present work, for the first time, the influence of aging has been investigated in the brain cortex of the Podolica cattle breed, through LC–MS/MS-based differential proteomics and the bioinformatic analysis approach (data are available via ProteomeXchange with identifier PXD044108), with the aim of identifying potential aging or longevity markers, also associated with a specific lifestyle. Results and discussion We found a significant down-regulation of proteins involved in cellular respiration, dendric spine development, synaptic vesicle transport, and myelination. On the other hand, together with a reduction of the neurofilament light chain, we observed an up-regulation of both GFAP and vimentin in the aged samples. In conclusion, our data pave the way for a better understanding of molecular mechanisms underlying brain aging in grazing cattle, which could allow strategies to be developed that are aimed at improving animal welfare and husbandry practices of dairy cattle from intensive livestock.